SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169114-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multi-Continuum Multi-Component Model for Enhanced Gas Recovery and CO2 Storage in Fractured Shale Gas Reservoirs

Abstract: Shale gas reservoirs have been proposed as feasible choices of location for injection of CO2 and/or N2 because this method could enhance recovery of natural gas resources, while at the same time sequester CO2 underground. In this paper, a fully coupled multi-continuum multi-component simulator which incorporates several transport/storage mechanisms is developed. To accurately capture physics behind the transport process in shale nanopores, Kundsen diffusion and gas slippage are included in the flow model. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…Many researchers found that the permeability of natural fractures is sensitive to pressure change (Jiang et al, 2014;Wu et al, 2013). Therefore, the pressure effect of the natural fracture is considered.…”
Section: Basic Equations For Comentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers found that the permeability of natural fractures is sensitive to pressure change (Jiang et al, 2014;Wu et al, 2013). Therefore, the pressure effect of the natural fracture is considered.…”
Section: Basic Equations For Comentioning
confidence: 99%
“…Only few people, till recently, have attempted to transform shale formations into repositories (Jiang et al, 2014;Tao and Clarens, 2013). It is pointed out in many published works that, kerogen contained in shale could result in a significant gas adsorption amount (Akkutlu and Fathi, 2011;Ambrose et al, 2010;Kang et al, 2010;Loucks et al, 2009;Sondergeld et al, 2010;Wang and Reed, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The state equation of SG is given as pM ZRT 11 g ρ = ( ) Many researchers found that the stress-sensitivity effect should be considered in low-permeability reservoir (Jiang et al, 2014;Wu et al, 2013). To simulate the stress-sensitivity effect, a practical equation with respect to pressure is applied (Pedrosa, 1986),…”
Section: Natural Fracture Subsystemmentioning
confidence: 99%
“…In , a hybrid multiple-continuum-medium modeling approach is developed to describe different types of fractures, including hydraulic fractures, natural fracture network, and micro fractures. In (Moinfar et al, 2013;Jiang et al, 2014), explicit fracture models are coupled with MINC model for the simulation of unconventional reservoirs. A unified framework model is developed in , which is able to incorporate known mechanisms and processes (gas adsorption and desorption, geomechanics effect, Klinkenberg or gas-slippage effect and non-Darcy flow) and use a hybrid fracturemodeling approach to simulate the unconventional gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%